MODEL KESIAPSIAGAAN BENCANA BERBASIS SEKOLAH MELALUI PROGRAM SATUAN PENDIDIKAN AMAN BENCANA DI KOTA TANGERANG - Rahmat, Hayatul Khairul; Frinaldi, Aldri; Rembrandt, R; Lanin, Dasman (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This study aims to analyze the implementation model of disaster management policies through the Disaster Safe School Program in Tangerang City. The research employed a qualitative method with a descriptive approach. The findings reveal that the implementation model of the disaster-safe educational unit policy generally adheres to disaster mitigation principles by applying regulations and procedures from both central and local levels. However, the fundamental measures and objectives of the Disaster Safe School Program in Tangerang City have not been fully realized. The allocation of policy resources, particularly budget implementation, remains limited, resulting in many disaster-prone schools lacking access to training. Furthermore, communication among organizations and implementing agencies during coordination has not been optimal. Outreach efforts by central and local authorities have yet to fully involve relevant stakeholders, such as the community. As a result, economically disadvantaged communities have limited understanding of the policy.